Tetrazine metallation boosts rate and regioselectivity of inverse electron demand Diels–Alder (iEDDA) addition of dienophiles. Issue 80 (9th September 2020) - Schnierle, Marc; Blickle, Svenja; Filippou, Vasileios; Ringenberg, Mark R.
Abstract : Reported herein is the coordination of rhenium complexes to tetrazine ligand in [ReCl(CO)3 (TzPy)] [1 ] (TzPy = 3-(2-pyridyl)-1, 2, 4, 5-tetrazine) and the rates of addition of different dienophiles to the tetrazine. Abstract : Reported herein is the coordination of rhenium complexes to tetrazine ligand in [ReCl(CO)3 (TzPy)] [1 ] (TzPy = 3-(2-pyridyl)-1, 2, 4, 5-tetrazine) and the rates of addition of different dienophiles to the tetrazine. Tetrazine coordiation lowers the Δ S ‡ contribution to Δ G ‡ for iEDDA addition.